Cost-Effectiveness Analysis of Mental Health Programs in Middle Eastern Conflict Zones - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This meta-analysis evaluates the cost-effectiveness of mental health interventions implemented in conflict-affected regions of the Middle East between 2010 and 2023, compiling data from 47 programs across eight countries. Statistical analysis reveals substantial variation in program effectiveness levels (Cohen's d = 0.78, 95% CI [0.65, 0.91], p < 0.001), with cognitive behavioral therapy (CBT) demonstrating the highest cost-effectiveness ratio, registering an ICER of 2,340 per QALY gained. Multilevel regression findings indicate that community-based intervention approaches consistently prove more cost-efficient than those conducted in clinical settings (β = 0.67, p < 0.001), yielding an average savings of 43% per participant. Remote teletherapy programs exhibit significant potential, particularly in regions with limited access to services, with an ROI reaching 1.89 (95% CI [1.65, 2.13]). The economic burden analysis estimates that untreated mental health conditions incur an average annual cost of 4,623 per individual, whereas intervention expenses amount to approximately 1,876 per patient per year, resulting in a benefit-cost ratio of 2.47. This study expands upon prior research by Tol et al. (2011) and McBain et al. (2016), which were limited to clinical outcomes without addressing the economic dimension. In contrast to the study by Reed et al. (1994), which explored general health economics within conflict zones, this research specifically quantifies the cost-effectiveness of mental health interventions in Middle Eastern conflict areas. It reveals that cultural adaptation within intervention programs can enhance return on investment by up to 31%. Finally, this review uniquely demonstrates that community-based mental health programs integrated within conflict zones can meet the cost-effectiveness thresholds recommended by WHO-CHOICE while maintaining a high level of clinical efficacy.